Estimating the monetary policy interest-rate-to-performance sensitivity of the European banking sector at the zero lower bound - Bernd Hayo; Kai Henseler; Marc Steffen Rapp (Philipps-University Marburg, School of Business and Economics, 2019)
Using an event-study design, we investigate monetary policy interest-rate-to-performance sensitivity of the European banking sector over the 07/2012-06/2017 period when interest rates were (close to) zero. We apply the Wordscores approach to introductory statements of ECB's Governing Council press conferences to estimate a "shadow prime rate". Based on short-run intraday event windows, we find shadow prime rate changes positively affect changes in the EURO-STOXX-Banks Future. Our findings add to the recent evidence documenting that banks benefit from increasing interest rate levels in a low-interest-rate environment.
Keywords: E43; E52; E58; G14; G21; 330; ECB; central bank communication; banking sector; interest rate sensitivity; textual analysis; Wordscores